Hypocrea rufa/Trichoderma viride: a reassessment, and description of five closely related species with and without warted conidia - Jaklitsch, Walter M. (CBS Fungal Biodiversity Centre, 2006)
The type species of the genus Hypocrea (Hypocreaceae, Hypocreales, Ascomycota, Fungi), H. rufa, is re-defined and epitypified using a combination of phenotype (morphology of teleomorphs and anamorphs, and characteristics in culture) and phylogenetic analyses of the translation-elongation factor 1α gene. Its anamorph, T. viride, the type species of Trichoderma, is re-described and epitypified. Eidamia viridescens is combined as Trichoderma viridescens and is recognised as one of the most morphologically and phylogenetically similar relatives of T. viride. Its teleomorph is newly described as Hypocrea viridescens. Contrary to frequent citations of H. rufa and T. viride in the literature, this species is relatively rare. Although both T. viride and T. viridescens have a wide geographic distribution, their greatest genetic diversity appears to be in Europe and North America. Hypocrea vinosa is characterised and its anamorph, T. vinosum sp. nov., is described. Conidia of T. vinosum are subglobose and warted. The new species T. gamsii is proposed. It shares eidamia-like morphology of conidiophores with T. viridescens, but it has smooth, ellipsoidal conidia that have the longest L/W ratio that we have seen in Trichoderma. Trichoderma scalesiae, an endophyte of trunks of Scalesia pedunculata in the Galapagos Islands, is described as new. It only produces conidia on a low-nutrient agar to which filter paper has been added. Additional phylogenetically distinct clades are recognised and provisionally delimited from the species here described. Trichoderma neokoningii, a T. koningii-like species, is described from a collection made in Peru on a fruit of Theobroma cacao infected with Moniliophthora roreri.